Investigation on the use of recycled plastics in the production of automobile parts - Gu, Fu (2015)
It has been reported that the use of recycled plastics is economical and environmentally-friendly. However, despite studies suggesting that properties of recycled plastics can be improved upon, there is very limited research which focuses on the application of recycled plastics in demanding industrial applications. Disappointingly recycled plastics have been almost totally neglected in the automobile production industry.